THE REALISATION OF CHILDREN’S RIGHT TO PARTICIPATION IN COMMUNITY CHILDREN’S CARE HOMES - Raudeliūnaitė, Rita; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article reveals the findings of a qualitative study the aim of which was to identify the realities of the realisation of the children’s right to participation in the community children’s care home (hereinafter referred to as CCCH). Research questions of the study: What are real possibilities for children to realise their right to participate in the decision taking in CCCH? How are children involved in decision taking? Nine social workers, working in CCCHs in different locations in Lithuania, participated in the study.The study revealed that to realise the child’s right for participation a positive attitude of an employee towards child’s participation. The positive attitude of an employee should be linked to a child-centre approach, which includes attentiveness to every child, openness to the child’s experience, opinion, non-dominance of an adult and the acknowledgement of the child being the expert of his situation. To realise the child’s right for participation establishment and maintenance of positive relationships with the child by employees which is linked to a respectful communication with the child, trust in the child and the child’s trust in the employee. It is also important to provide the child with information regarding his right for participation by informing that employees are ready to listen to him and that he has a right to express his opinion on different topics regarding himself. Another important aspect of the realisation of the child’s right for participation is cooperation with the child which is expressed through the provision of information in the manner which is understandable to the child, his empowerment to participate when taking decisions, listening to his opinion, taking into consideration his opinion, in order to ensure his best interests, the analysis of situations and discussions with children when taking decisions, assistance, but not substitutionary help when the child takes decisions. The study revealed that CCCHs create conditions for the child’s right for participation to be realised in his daily activity which is expressed the child’s participation when drawing up CCCH’s rules and adhering to them, planning and organising his leisure time, the child’s involvement in the creation and maintenance of personal and common spaces, daily choruses.